1999
DOI: 10.1177/135245859900500507
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine analysis in multiple sclerosis by competitive RT - PCR: A decreased expression of IL-10 and an increased expression of TNF-α in chronic progression

Abstract: Multiple sclerosis (MS) is an inflammatory, demyelinating disease that is specific to the central nervous system. Cytokines are thought to be key mediators of the autoimmune attack against central nervous system myelin in MS. To investigate the involvement of cytokines in MS, the mRNA levels of interferon gamma (IFN-gamma), tumor necrosis factor alpha (TNF-alpha), interleukin-4 (IL-4) and interleukin-10 (IL-10) in peripheral blood mononuclear cells without stimulation in vitro were quantified by a competitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…30 There are conflicting data on IFN-® levels in MS. Elevated numbers of IFN-® mRNA-expressing blood MNCs 31 and increased serum IFN-® levels, compared to findings in controls, 32 have been reported in MS. At the same time, other studies found no difference between MS patients and controls with regard to either the percentage of IFN-®-expressing cells in blood detected by flow cytometry 33 or the blood levels of IFN-® mRNA. 34,35 Using ELISPOT assays, we found no difference in numbers of blood MNC spontaneously secreting IFN-® between MS patients and controls 36,37 (Figure 5), corroborating findings from previous reports. 10 ± 13 TNF-¬ TNF-a is a potent proinflammatory cytokine.…”
Section: Ifn-®supporting
confidence: 94%
“…30 There are conflicting data on IFN-® levels in MS. Elevated numbers of IFN-® mRNA-expressing blood MNCs 31 and increased serum IFN-® levels, compared to findings in controls, 32 have been reported in MS. At the same time, other studies found no difference between MS patients and controls with regard to either the percentage of IFN-®-expressing cells in blood detected by flow cytometry 33 or the blood levels of IFN-® mRNA. 34,35 Using ELISPOT assays, we found no difference in numbers of blood MNC spontaneously secreting IFN-® between MS patients and controls 36,37 (Figure 5), corroborating findings from previous reports. 10 ± 13 TNF-¬ TNF-a is a potent proinflammatory cytokine.…”
Section: Ifn-®supporting
confidence: 94%
“…We did observe that IL10 was higher in summer, in line with previous work finding vitamin D treatment increases production of IL-10,28 this suggesting that not being able to find a link between IL-10 and relapse was not due to a deficiency in our measurement of IL-10. Similarly, IL-4's absence of association with relapse in qualitative analysis is unsurprising in comparison with the literature which has shown no consistent evidence of association with MS risk26 or clinical course 8 27 29…”
Section: Discussionmentioning
confidence: 81%
“…As their induction requires either the presence of IL-10 at activation or costimulation via CD46 (in humans [35]), it is likely that they represent cytokine deviated conventional CD4 T cells. Patients with multiple sclerosis (MS) have fewer IL-10 secreting peripheral blood mononuclear cells (PBMC) when compared with healthy controls [36,37] and, while IL-10 expression is reduced before clinical relapse, there is an increase in PBMC expressing IL-10 transcripts [38]. In vitro CD46-mediated induction of Tr1-like cells from CD4 þ cells from patients with MS and control individuals, suggested that the IL-10R signalling pathway was impaired in patients.…”
Section: Tr1 Cellsmentioning
confidence: 98%